If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(9 + -1y) + 4y = 36 (9 * 4 + -1y * 4) + 4y = 36 (36 + -4y) + 4y = 36 Combine like terms: -4y + 4y = 0 36 + 0 = 36 36 = 36 Add '-36' to each side of the equation. 36 + -36 = 36 + -36 Combine like terms: 36 + -36 = 0 0 = 36 + -36 Combine like terms: 36 + -36 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 0=(x^2-31x-32)/40 | | 9d+8+6=24 | | 9d+8+2+2+2=24 | | 49yy+1=0 | | 49y+1=0 | | 2x-8=5x-2 | | x+(x/2)=134627 | | 2(3x2-5)+3x1/3 | | (b-3)(b-3)=9 | | 9d+8=24 | | 5y=-5x+15 | | 9d=10 | | 150+50t=350 | | -21+2x+8x^2= | | -4q-15=q | | 6r^2+2r-24= | | 1/2=y/2 | | 25a-8=8 | | H=-16t^2-16t+60 | | n*n^9= | | (2x^-3/3y^-4)^-2 | | X+3/8=5/x-3 | | V-9=10 | | a-14=-26 | | 8+y=5 | | 3w-14=13 | | x^2+175=0 | | 2+x=6x-28 | | e^2x=4 | | 18x-9/3= | | 1/4+1/5=x/2 | | 3(5)+6(-2.4)= |